Effect of Li(I) and TiO2 on the Upconversion Luminance of Pr:Y2SiO5 and Its Photodegradation on Nitrobenzene Wastewater - Yi Yang; Guang-Zhi Xia; Cheng Liu; Jin-Hua Zhang; Lian-Jun Wang (Journal of Chemistry)
Based on the substrate of Pr:Y2SiO5 upconversion nanomaterials, lithium ion Li(I) doped Pr:Y2SiO5 and TiO2 nanofilm coated Li,Pr:Y2SiO5 composites were prepared by using a sol-gel method. X-ray diffractometer, SEM, and fluorescence spectrometer have been employed to test the crystal structure, microimages, and upconversion luminescence performances. The doping of Li(I) affects highly the crystal transition of Pr:Y2SiO5 and X2-Y2SiO5 phase was well formed by doping 8% Li(I). Furthermore, the doping of Li(I) also brings high luminance intensity of Pr:Y2SiO5 and contributes to a maximum intensity of 9.76 × 106 cps doped 8%. Too much of Li(I) doping would result in big crystal size and fluorescence quenching of Pr:Y2SiO5 material. However, the coating of TiO2 nanofilm is not helping in increasing the upconversion fluorescence of Li,Pr:Y2SiO5 but is promoting the full use of the fluorescence. The luminescence intensities of TiO2/Li,Pr:Y2SiO5 composites are getting down sharply with the coating amount since the luminescence emitted by Li,Pr:Y2SiO5 is quickly adsorbed in situ by the TiO2 coating film. With the optimum coating concentration of 1%, the TiO2/Li,Pr:Y2SiO5 composite shows excellent photodegradation performances on nitrobenzene wastewater, though it shows a low luminescence intensity. For 5 mg/L nitrobenzene wastewater, the composite presents a photodegradation rate of 97.08% in 4 hours.